The international responsibility of the Statefor the delay in a judicial decision making.(Case García Mateos against Spain) (2014)
This article refers to conduct that eventually generates State responsibility under international law, with an emphasis on the of ficials of the judicial branch for the delay in making a final decision. Subsequently describes the details of a case brought before the European Court of Human Rights in the decision taken a benchmark that in terms of access to an effective judicial remedy must link States within a framework of respect for human rights and access to justice, especially when judges act slowly and at the same time they do not recognize the pursuit of material justice.